ANALISIS HUBUNGAN INDEKS HARGA SAHAM GLOBAL DENGAN INDEKS HARGA SAHAM GABUNGAN (IHSG) - Adrianda Anwar; Animah Animah (Universitas Muhammadiyah Jember, 2023)
This research aims to examine the relationship between global stock price indices (DJIA, SP 500, FTSE 100, CAC 40, DAX, Hangseng, Nikkei 225, SSEI, STI, ASX 200) with the JCI both jointly and partially. The sample used in this research is global index monthly data from January 2000 to December 2016 with 204 samples. The measurement tool used in this research is multiple linear regression analysis using Stata/SE Version 14.2. The research results show that together there is a relationship between the global stock price index and the JCI. Partially, the SP 500 index, the FTSE 100 index, the DAX index, the SSEI index, the STI index, and the ASX 200 index have a significant positive relationship with the JCI. Meanwhile, the DJIA index, CAC index, Hangseng index, and Nikkei 225 index have a significant negative relationship with the JCI. The contribution of the influence of the global stock price index to the JCI is 99.2%, the rest is influenced by other factors.